ESSENTIA OF HUMAN BEING AND ONTO-THEOLOGICAL ESSE OF METAPHYSICS: HISTORICAL AND PHILOSOPHICAL CONTEXT - N. V. Skrytska (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The purpose of research is to show essential of the human being on the level of philosophical analysis, and to define the necessity of ontho-theological essence of metaphysic on the basis of the historical and philosophical context. Methology. For the sake of disclosure multifacetedness human being used such methods: the method of terminological analysis, hermeneutic method, a method of classification, historical method, philosophical method, dialectical method, the method of generalization, the method of abstraction, the method of idealization, phenomenological method. Scientific novelty. On the basis of historico-philosophical researches it is carried out the analysis of the concepts essentia of human being, proceeding not only from the metaphysical point of view, but also with anthropological, axiological and gnoseological. It is proved that, despite of metaphysics accessory as abstract knowledge to different philosophical sections, everything the main thing remains the appeal to primary sources. After all in our world of cruelty, neglect, loss spirituality the main thing is not to lose the spiritual soil and the appeal to God.